Vitamin D supplementation and mortality risk in chronic kidney disease a meta-analysis - Aljahdaly, Atef H.; ALMALKI, KHALID S.; ALTHEEB, HIFTHI K.AL; Alshehail, Dr. Shams Mohammed; Makki, Wejdan Ali Sulieman; Aljedaani, Shaher Mohammed; Al-smari, Nora Abdullah; AlKhayri, Dalal Ali; ALGHAMDI, ALI ABDUULAH; ALMEWALED, EBTHAL AHMED; et al. (Journal of Posthumanism, 2024)
Background: Chronic kidney disease (CKD) is a greatly prevalent condition worldwide in which the kidneys are functionally and/or structurally damaged. Vitamin D deficiency is very common in CKD, influencing over eighty percent of cases in pre-dialysis.Aim: To evaluate the impact of vit. D supplementation on mortality risk and related clinical results in patients with CKD.Patients and methods: Cochrane Library, PubMed, Embase, and Web of Science have been searched up to December 2021 for observational and interventional studies comparing vitamin D non-users and users in adult CKD cases. The 1ry result was all-cause mortality; 2ry results involved dialysis vintage, phosphorus, calcium, hemoglobin, intact parathyroid hormone (iPTH), alkaline phosphatase, lipid profile, and albumin. Data were pooled utilizing Review Manager 5.4.1, with fixed- or random-influences models regarding heterogeneity.Results: Eight studies involving 57,429 patients were included. Vit.D supplementation has been correlated with a significant reduction in mortality risk (OR = 0.54, 95% CI = 0.35–0.81, p = 0.003). Significant reductions in iPTH were observed, while other biochemical parameters showed insignificant variances between groups.Conclusion: Vitamin D supplementation in CKD is correlated with improved survival and favorable effects on parathyroid hormone, supporting its therapeutic role.